2010
DOI: 10.1073/pnas.1010165107
|View full text |Cite
|
Sign up to set email alerts
|

Single-electron pulses for ultrafast diffraction

Abstract: Visualization of atomic-scale structural motion by ultrafast electron diffraction and microscopy requires electron packets of shortest duration and highest coherence. We report on the generation and application of single-electron pulses for this purpose. Photoelectric emission from metal surfaces is studied with tunable ultraviolet pulses in the femtosecond regime. The bandwidth, efficiency, coherence, and electron pulse duration are investigated in dependence on excitation wavelength, intensity, and laser ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
161
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(171 citation statements)
references
References 52 publications
3
161
0
Order By: Relevance
“…Temporal compression techniques can be used to obtain femtosecond many-electron pulses at a distant sample 15 , but have yet to be demonstrated for low electron energies. Alternatively, space charge broadening can be eliminated by using single electron pulses at high repetition rates 16,17 . Still, achieving femtosecond time resolution with dispersing sub-keV single electron pulses further requires considerable reduction of the propagation distances 18,19 .…”
mentioning
confidence: 99%
“…Temporal compression techniques can be used to obtain femtosecond many-electron pulses at a distant sample 15 , but have yet to be demonstrated for low electron energies. Alternatively, space charge broadening can be eliminated by using single electron pulses at high repetition rates 16,17 . Still, achieving femtosecond time resolution with dispersing sub-keV single electron pulses further requires considerable reduction of the propagation distances 18,19 .…”
mentioning
confidence: 99%
“…Also, diffraction images have identified transient molecular structures [8] and established evidence of deformation and dissociation of molecules interacting with laser pulses [9]. Nowadays, electron pulses with femtosecond (fs) duration have been reported [10][11][12][13][14]. Recently, single-electron pulses with a full-width at half-maximum (fwhm) duration of 28 fs have been demonstrated [15].…”
mentioning
confidence: 99%
“…Combining conventional electron or X-ray beam methods with femtosecond laser pulses provides improved temporal resolutions for molecular dynamics investigation approaching atomic time scales [23][24][25][26] . However, recent experiments [27][28][29][30][31] demonstrated that intense, isolated femtosecond pulses alone are sufficient for imaging simple molecules via a strong-field three-step process 32,33 (see Supplementary Discussion).…”
mentioning
confidence: 99%